The larval development of the mud shrimp Upogebia issaeffi (Balss, 1913) (Decapoda: Gebiidea: Upogebiidae) reared under laboratory conditions - Kornienko, Elena S.; Korn, Olga M.; Demchuk, Darya D. (Zootaxa, 2012)
Larval development of the mud shrimp Upogebia issaeffi (Balss, 1913) (Decapoda: Gebiidea: Upogebiidae) is describedand illustrated for the first time from material reared in the laboratory. The development includes four zoeal and a singlemegalopal stages. At 20–22°C the first megalopa was attained 12 days after hatching. U. issaeffi is distinguished from U.major, the second upogebiid species inhabiting Russian waters of the Sea of Japan, by the presence of the fourth zoeal stage and considerably more intensive larval setation.